Lower North Shore Housing Needs Assessment - Kippen, Kayla (2019)
Communities in rural remote regions often struggle with access to services across the province and other parts of Canada. These access issues are often worsened during times of crisis. A significant problem facing rural communities is the current housing structure for vulnerable people. For example, those requiring palliative care services, or facing mental health and dependency issues, are particularly confronted with issues when trying to secure or obtain stable housing, or access to supportive housing programs and services. In 2017, the federal government announced its first ever National Housing Strategy for Canadians, with a goal of making sure Canadians across the country can access housing that meets their needs and that they can afford. With the witnessed economic downturns, poverty and unemployment rates of the region, it was necessary to investigate whether the Lower North Shore was also providing access to housing that meets the needs of all citizens.

Project Report : Presented by Lower North Shore Housing Corporation - Kippen, Kayla (2018)
The Corporation d’habitation de la Basse-Cote-Nord, or Lower North Shore Housing Corporation (LNSHC), was legally registered as a non-profit organization in October 2018. The Housing Corporation was an initiative presented by the Coasters Association, and other organizations, to develop an affiliate corporation that would manage housing programs and services for the region. Over the past year of the project, there have been many achievements and challenges. There has been a great amount of effort put in by all those associated with this project. It is clear that the Housing Corporation is an important initiative to the representatives and citizens of the Lower North Shore. It is for this reason that we must continue to work towards exploring funding avenues to support the continuance of this project.